(untitled) (Journal of Hama University, 2019)
The study was included 12 community regions in Hama City in order to study the epidemiological prevalence of Cutaneous Leishmaniasis (CL) in administration geography of the city. The study determined the descriptive epidemiology evaluation of the prevalence of CL in all study regions with Spatial-Global map of the study determinants in addition to determine the time Spatial of the Occurrence of morbidity rates individually and overall as administration regions. The study reported the overall prevalence 43.52%. The most increase the level of prevalence was in March 96.21%. As the study reported the higher level of observation prevalence in 2 regions (Tarek Halb and Alquosuer) that was, there are close to Orients river and populated regions with community near to local populations in individual regions.